2023
DOI: 10.1001/jama.2023.14590
|View full text |Cite
|
Sign up to set email alerts
|

Intensive vs Conventional Blood Pressure Lowering After Endovascular Thrombectomy in Acute Ischemic Stroke

Hyo Suk Nam,
Young Dae Kim,
JoonNyung Heo
et al.

Abstract: ImportanceOptimal blood pressure (BP) control after successful reperfusion with endovascular thrombectomy (EVT) for patients with acute ischemic stroke is unclear.ObjectiveTo determine whether intensive BP management during the first 24 hours after successful reperfusion leads to better clinical outcomes than conventional BP management in patients who underwent EVT.Design, Setting, and ParticipantsMulticenter, randomized, open-label trial with a blinded end-point evaluation, conducted across 19 stroke centers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…During the title and abstract screening phase, 190 records were excluded, leaving 4 records that underwent a full-text article assessment to ascertain eligibility. None of the full-text articles failed to meet the inclusion criteria, resulting in the inclusion of all 4 studies in our quantitative synthesis . The studies were published between 2021 and 2023 and were conducted in China, France, South Korea, and the US.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…During the title and abstract screening phase, 190 records were excluded, leaving 4 records that underwent a full-text article assessment to ascertain eligibility. None of the full-text articles failed to meet the inclusion criteria, resulting in the inclusion of all 4 studies in our quantitative synthesis . The studies were published between 2021 and 2023 and were conducted in China, France, South Korea, and the US.…”
Section: Resultsmentioning
confidence: 99%
“…A compilation of the 4 studies included in our analysis, along with their respective evaluations of bias across various domains using the RoB 2, can be accessed in eFigures 1 and 2 in Supplement 1. Among these studies, our assessment revealed that 3 of them had a moderate risk of bias, while one was categorized as having a low risk of bias. Notably, the domains demonstrating more concerns were bias arising from the randomization process and bias in measurement of the outcome.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations